Factors Associated with Non-Adherence among Type-2 Diabetes Mellitus Patients: Results from Primary Care Clinics in Faisalabad Pakistan - Yousaf Ikram, Muhammad Masood Ahmed, Muhammad Tariq, Fakhira Jabeen, Iqra Tariq, Muhammad Usman (Pakistan Journal of Medical & Health Sciences, 2022)
Background: The global increase in rates of type 2 diabetes has become a serious public health concern. Adherence to treatment is an important predictor of glycemic control. Poor adherence to treatment regimens is a major clinical problem in the management of diabetes. This study aims to identify the associated factors with non adherence to diabetes treatment among patients of type 2 diabetes. Study Design: Cross-sectional study Place and Duration of Study: Primary Care Clinics of Faisalabad, Pakistan from 1stDecember 2020 to 28thFebruary 2021. Methodology: Five hundred and forty nine adults (>18 years of age) confirmed cases of type 2 diabetes were consecutively approached. Results: 56.6% were less than 50 and 43.4% were more than 50 years of age and 59.9% of the participants were females. About 42.7% of the participants were non-adherent to diabetes treatment. Participants aged less than 50 years were two times more at risk of being non-adherent (aOR: 1.88; 95% CI: 1.29-2.76). Level of education and duration to diagnosis of DM were marginally significant (p-0.07, p-0.06) to non-adherence respectively. Conclusion: Adherence to treatment of diabetes and to achieve glycemic control is a challenging concern across countries including Pakistan. Therefore, aggressive counseling about benefits of regular exercise and diet with special emphasis on younger patients who recently diagnosed with diabetes should be implemented. Governments should reduce the costs of treatment to make it cheap and affordable and more parks, walking tracks should be introduced to make it accessible for population.